Comparative Assessment of Energy Security Level: The Case of the South Caucasus Countries - Aliyev, Shafa; Gulaliyev, Mayis; Purhani, Safar; Mehdiyeva, Gulsura; Mustafayev, Elchin (International Journal of Energy Economics and Policy, 2024)
The paper compares the energy security of three South Caucasus countries - Azerbaijan, Georgia, and Armenia. These countries differ from each other due to the use of different energy sources. The investigation used 28 indicators classified into six groups based on World Bank data to assess energy security. Indicators for each group were assessed as “stimulating” or “not stimulating” energy security. According to the results, Georgian’s energy security is less risky because of it uses renewable energy sources. Ensuring long-term energy security in Azerbaijan requires greater use of renewable energy sources. Armenia’s energy security is at higher risk due to its higher dependence on imports and poor use of renewable resources.